Analisis Faktor yang Mempengaruhi Efektivitas Komunikasi melalui WhatsApp pada CV Mulia Buana Jaya - Ponto, Klara Euigenia; Wijaya, I Gusti Ngurah Satria; Dunggio, Maryam (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2025)
The development of communication technology has brought innovations such as digital platforms communication like WhatsApp, making communication easier across distances. CV Mulia Buana Jaya uses WhatsApp for both internal and external communication. Although it offers convenience and speed, its use in supporting corporate communication requires evaluation. This study aims to analyze the factors influencing the utilization of WhatsApp in internal and external communication in the company and their impact on communication effectiveness. The novelty of this study is mix method approach, combining qualitative method using thematic analysis through and and quantitative method using multiple linear regression analysis. Data collection was done through semi-structured interviews with six informants (purposive sampling) and questionnaires distributed to 60 respondents (Slovin's formula and stratified random sampling). The data provided by respondents used a Likert scale and analyzed with IBM SPSS Statistics 25. The result of this research findings reveal three key factors influencing the utilization of WhatsApp in internal and external communication in company is ease of use, usefulness, and security. These factors positively and significantly impact communication effectiveness, both individually and collectively. The findings offer practical implications for the company in evaluating and optimizing the use of WhatsApp to improve internal and external communication effectiveness.